The Position of the United States from Britain in the discussions of British Evacuation from Egypt (1946-1952) - ميسون عباس حسين (College of Education for Women, 2019)
Many reasons combined behind the Standing of U.S. against Britain in its aggression against Egypt in 1956; the consensus of world opinion on the need to stop the aggression and the fear of the Soviet military intervention which mean a new world war. United States desired to weaken British influences in the region in general to get new oil gains in the Arabian Gulf and Egypt at the expense of Britain. The exiting of Britain from the area served U.S. strategic interests in the Middle East in general and Egypt in particular to keep the flow of oil for U.S advantage. The United States wanted to keep its image in the region to apply its future political projects including Eisenhower Project, which intended to take the position of British in the region by the United States to get more air bases and strategic locations to be as the second line of the U.S. bases in Turkey near the borders of the Soviet Union. Egypt refused the idea because it realized that the project were found to serve the goals of Western countries in the Arab world as it involved political constraints which make Egypt linked to the United States. The British government were divided into opponents and supporters towards the project Eisenhower. Opponent found that the U.S. wants to bring out Britain and all colonies from the Middle East, while supporter found the project was as an opportunity to re the US-British relations to what it was before the Suez crisis.The United States did not want to involve Britain in the political projects because U.S wanted to dominate the region by itself. United States succeeded and since that time it dominated the region solely and exclusively.